Challenges in understanding the structure/activity relationship of Aβ oligomers - Albert W. Pilkington IV; Justin Legleiter (AIMS Biophysics, 2019)
A major hallmark of Alzheimer’s disease (AD) is the accumulation and deposition of fibrillar aggregates of the amyloid-b (Ab) peptide into neuritic plaques. These amyloid deposits were thought to play a central role in AD; however, the correlation between plaque load and disease is weak. Increasing evidence supports the notion that a variety of small, globular aggregates of Ab, referred to broadly as Ab oligomers (AbO), may in fact be the primary culprits associated with neurotoxicity. Evaluation of AbO structure and physiological activity is complicated by their metastability, heterogeneity, complex aggregation pathways, and dependence on experimental conditions. Numerous different types of oligomers have been reported, and these have been associated with varying degrees of toxicity and modes of interaction. Here, we briefly review AbOs with a focus on their formation, structure, and biophysical methods applied to their investigation.